2015
DOI: 10.1515/ohs-2015-0041
|View full text |Cite
|
Sign up to set email alerts
|

Driving factors affecting spatial and temporal variations in the structure of phytoplankton functional groups in a temperate reservoir

Abstract: During the twenty-five years of existence, water quality has declined and severe blooms of cyanobacteria have occurred in the Grlište Reservoir. Changes in phytoplankton functional groups over time and along horizontal and vertical gradients were investigated in the course of a one-year study in this water-supply reservoir. We identified 19 dominant taxa, classified into 12 phytoplankton associations. The presence of the codons C, P, D and S1 differentiated the transitional from the lacustrine part of the rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…Bacillariophyta and Chlorophyta dominated the dry season (November and April) when the water column was mixed, C. meneghiniana, M. granulata, and Chlorella vulgaris were the dominant species. The results were consistent with other studies [14,18,44] on fresh water aquatic ecosystem, that is, mixing regime, low light availability and low temperature were contributed to phytoplankton dynamic during dry season (October to February). In addition, C. ovata belonging to Cryptophyta was the most abundant species in February, standing within other studies [18,20] that C. ovata could adapt to high inorganic turbidity.…”
Section: Effects Of Nutrient and Light Availability On Phytoplankton supporting
confidence: 93%
See 1 more Smart Citation
“…Bacillariophyta and Chlorophyta dominated the dry season (November and April) when the water column was mixed, C. meneghiniana, M. granulata, and Chlorella vulgaris were the dominant species. The results were consistent with other studies [14,18,44] on fresh water aquatic ecosystem, that is, mixing regime, low light availability and low temperature were contributed to phytoplankton dynamic during dry season (October to February). In addition, C. ovata belonging to Cryptophyta was the most abundant species in February, standing within other studies [18,20] that C. ovata could adapt to high inorganic turbidity.…”
Section: Effects Of Nutrient and Light Availability On Phytoplankton supporting
confidence: 93%
“…Studies have indicated that light and nutrient availability, temperature, conductivity, water stability and retention time are regarded as important chemical and physical factors influencing phytoplankton structure and composition in reservoir ecosystems [10][11][12][13]. Ciric et al [14] in their study found that thermal stratification and physical mixing processes, and reduction versus oxidation processes were the two main factors that explain variability in phytoplankton in a temperate reservoir. Water column stability and water renewal rate were regarded as factors controlling phytoplankton tropical high-mountain drinking-water reservoirs [15].…”
Section: Introductionmentioning
confidence: 99%
“…Turbidity was higher in the rainy season, possibly due to higher incoming flows or run-offs. These results were consistent with those observed by Ciric et al [41] and Toor et al [35]. The aforementioned behavior was similar for chlorophyll-a.…”
Section: Temporal and Spatial Variations Of Water Quality In The Alm supporting
confidence: 93%
“…using Equations (1)-(4) with the mean values of chlorophyll-a, total phosphorus, total nitrogen, and Secchi disk depth (SD) during the study period (2012-2018). According to the CMTSI obtained, results indicate that the trophic state of the ALM reservoir was maintained as mesotrophic (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) over time ( Figure 7) [30]. The value of the CMTSI was similar in the four sampling sites.…”
Section: Trophic Status Of the Reservoirmentioning
confidence: 92%
“…However, several studies dealt with the effect of boiling time on metal release from herbs, and others on the influence of the acidity of the medium (i.e. Mehra and Baker 2007;Özcan et al 2008;Altıntıg, Altundag, and Tuzen 2014;Sembratowicz and Rusinek-Prystupa 2014;Garba et al 2015;Jeszka-Skowron, Krawczyk, and Zgoła-Grześkowiak 2015;Pantelić et al 2015). This study is designed to update knowledge and determine the levels of Fe, Zn, Mn, Cu, Cr, Ni, Pb, As, and Cd in green and eight herbal teas that include hawthorn, St John's wort, nettle, elderflower, bearberry, thyme, yarrow, and mint.…”
Section: Introductionmentioning
confidence: 99%